1992
DOI: 10.1029/92tc00596
|View full text |Cite
|
Sign up to set email alerts
|

The tectonic history of the southwestern UNited States and Sonora, Mexico, during the past 100 M.Y.

Abstract: The area between the Colorado Plateau on the north, New Mexico and Chihuahua to the east, and southern and Baja California to the southwest has undergone a complicated thermal and tectonic history climaxing in medial Cretaceous time and manifested in a sequence of events which continue to the present time, independent of plate boundary transform faulting. This sustained sequence of events was initiated by subduction‐related magmatic emplacement, largely between 120 and 50 Ma, beginning in the west and sweeping… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…The presence of high topography along this margin is geologically recorded by northeast-flowing paleorivers (Young & Hartman 2014). Gastil et al (1992) suggested a highland on the order of 5 km high based on remnants of these paleorivers (Rim Gravels) on the northern flank of the highland and unconformities in southern California. J.B. utilized whole-rock La/Yb ratios from continental arc rocks in southern Arizona and northern Sonora to estimate crustal paleothickness of 62-48 km from 76 to 61 Ma.…”
Section: Laramide Orogeny (Ca 90-40 Ma)mentioning
confidence: 99%
“…The presence of high topography along this margin is geologically recorded by northeast-flowing paleorivers (Young & Hartman 2014). Gastil et al (1992) suggested a highland on the order of 5 km high based on remnants of these paleorivers (Rim Gravels) on the northern flank of the highland and unconformities in southern California. J.B. utilized whole-rock La/Yb ratios from continental arc rocks in southern Arizona and northern Sonora to estimate crustal paleothickness of 62-48 km from 76 to 61 Ma.…”
Section: Laramide Orogeny (Ca 90-40 Ma)mentioning
confidence: 99%
“…Cartographers generally recognize the region, from north to south, as the Coachella, Imperial, and Mexicali Valleys, as well as the floodplain of the Colorado River that abuts the Upper Gulf of California. Sediments in the Salton Trough have accumulated atop a Paleozoic basement of limestone, sandstone, conglomerate, and metamorphic rocks (Gastil et al 1992, Delgado-Granados et al 1994, Nations and Gauna 1998, Fletcher and Munguía 2000, Bialas and Buck 2009. The sediment-basement interface is irregular and occurs at depths from 1.4 to 5.6 km (Anderson et al 2003, Lovely et al 2006, Crowell et al 2013, Pacheco et al 2006.…”
Section: The Colorado River Delta -A Highly Variable Environmentmentioning
confidence: 99%
“…The top of the subducting plate was at 35 km depth, some 150-180 km inland from the trench, and led to the underplating of trench sediment beneath Cordilleran arc-related rocks. This architecture has been documented in southern California (Burchfiel and Davis 1975;Gastil et al 1992), but no better, more coherent exposures of the deep roots of the system exist than those in the central California Coast Range.…”
Section: Introductionmentioning
confidence: 99%